An empirical study on the decoupling movements between corporate bond and CDS spreads - Ioana Alexopoulou; Magnus Andersson; Oana Maria Georgescu (European Central Bank (ECB), 2009)
Applied to the European markets, this paper analyzes the price of credit risk on the Credit Default Swap (CDS) and corporate bond markets by comparing the sensitivity of the credit spreads on each market to systematic, idiosyncratic risk factors and liquidity. Our analysis confirms the existence of a long-run relationship between the two markets, and the tendency for CDS markets to lead corporate bond markets in terms of price discovery. We find that the outbreak of the financial turmoil in the summer of 2007 induced a substantial increase in risk aversion and a shift in the pricing of credit risk, with CDS markets becoming more sensitive to systematic risk while cash bond markets priced in more information about liquidity and idiosyncratic risk. Moreover, the financial turbulence also brought about a systematic disconnection between the two markets caused by the significant change in the lead-lag relationship, with CDS markets always leading the cash bond markets.
Keywords: G12; G14; G15; 330; corporate bond spreads; Credit Default Swap Spreads; liquidity; Unternehmensanleihe; Kreditderivat; Kreditversicherung; Kreditrisiko; EU-Staaten